![{x}^{2} - x - k = (x + 3)(x - 4) {x}^{2} - x - k = (x + 3)(x - 4)](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+-+x+-+k+%3D+%28x+%2B+3%29%28x+-+4%29)
give me correct answer please
Answers
Answered by
1
Explanation:
x²-x-k=(x+3)(x-4)
x²-x-k=x²-4x+3x-12
-x-k=-x-12
-k=-12
k=12
Follow me
Answered by
2
It's simple
x²-x-k=x²-4x+3x-12
x²-x+k=x²-4x+3x-12x²-x++k=x²-x-12
so by comparing both sides we get
-k=-12
k=12
Similar questions
Math,
5 months ago
Math,
5 months ago
English,
5 months ago
Math,
10 months ago
Social Sciences,
10 months ago
Computer Science,
1 year ago